Hungarian Monitoring, 9 July 1990 . [Magyar rádiófigyelő], 1990. július 9 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - CPSU elects new leader - Jaruzelski supports Mazowiecki - Bulgarian demonstration in support of Socialist Party president Domestic Affairs: - Árpád Göncz travels to Czechoslovakia - FRG defense minister in Budapest - Hungarian delegation travels to Moscow - Sports plane crashes at Hatvan - More refugees from Tirana may come - Vatra Românească protest against Hungarian-language education Economy: - Reduction in Soviet mineral oil transports - UN experts' Budapest conference on economic development - Rise in coal prices - On the entrepreneurial development fund Külpolitika: - Az SZKP új vezetőket választ - Jaruzelski támogatja Mazowieckit - Bolgár tüntetés a szocialista párti elnök mellett Belpolitika: - Göncz Árpád Csehszlovákiába utazik - Budapesten az NSZK védelmi minisztere - Magyar küldöttség utazik Moszkvába - Sportrepülőgép lezuhanása Hatvannál - Tiranából újabb menekültek jöhetnek - Vatra Romaneasca tiltakozás a magyar nyelvű oktatás ellen Gazdaság: - Szovjet kőolajszállítások csökkentése - ENSZ szakértők budapesti tanácskozása a gazdaságfejlesztésről - Emelkedik a szén ára - A vállalkozásfejlesztési alapról